A clinical investigation comparing the efficacy of composite resin vs. resin-infiltrated ceramic CAD/CAM onlays for restoring permanent first molars affected by severe molar-incisor hypomineralization - Zhao, Shuya; Ren, Yujia; Yin, Yuling; Xing, Xianghui (Frontiers in Dental Medicine, 2025)
BackgroundThe restoration of severely affected first permanent molars in patients with molar-incisor hypomineralization (MIH) presents significant clinical challenges yet remains essential.AimThe purpose of this randomized controlled trial is to evaluate and compare the clinical performance of the traditional composite resin restorations and the resin-infiltrated ceramic Computer-Aided Design/Computer-Aided Manufacturing onlays on permanent first molars affected with severe MIH.MethodsEighty permanent first molars affected with severe MIH in 79 participants (mean age, 8.6 years) were randomly allocated to the two treatment groups: the composite resin restoration (CR Group, n = 40) or the resin-infiltrated ceramic CAD/CAM onlays (Lava Ultimate, LU Group, n = 40). After complete removal of MIH-affected tissue and tooth preparation, the CR group received direct composite fillings, while the LU group received adhesively cemented CAD/CAM onlays. Follow-up assessments were conducted at 6 months (n = 80 restorations), 12 months (n = 78), and 24 months (n = 68). The restorations were evaluated according to the modified United States Public Health Service (USPHS) criteria with grades Alpha to Delta. Rating with Charlie or Delta was defined as clinical failure. Outcomes assessed included retention, marginal adaptation, secondary caries, color match, and surface roughness. Data were statistically analyzed using Chi-square test, Fisher's exact test, Kaplan–Meier and Log-rank test.ResultsCumulative survival rates at 6-month (CR Group: 100%; LU Group: 100%), 12-month (CR Group: 89.7%; LU Group: 94.9%), and 24-month (CR Group: 73.4%; LU Group: 86.7%) intervals showed no statistically significant difference (Log-rank test: χ2 = 1.9, p = 0.17). However, the LU Group demonstrated superior performance in clinical indicators including anatomic form maintenance (p = 0.02) and recurrent caries incidence (p = 0.04) than the CR Group.ConclusionBoth the composite resin restorations and the resin-infiltrated ceramic CAD/CAM onlays can offer relatively reliable restorative approaches for first molars severely affected by Molar Incisor Hypomineralization (MIH). Adhesive bonding procedures need special attention and a regular maintenance is suggested. A long follow-up is proposed to draw further conclusions.